The wilderness of the upper Yukon; a hunter's explorations for wild sheep in sub-arctic mountains - Sheldon, Charles, 1867-1928 (C. Scribner's sons, 1911)
A record of field experiences while engaged in studying the color variations of the wild sheep of Yukon Territory. It is an attempt to give a detailed account strictly from the point of view of a hunter interested in natural history.